Produção de bioetanol a partir de resíduos de frutas - Favaretto, Danúbia Paula Cadore (2023)
Fossil fuels, in addition to being irrenewable, emit polluting gases, which contribute to to the greenhouse effect, they accelerate global warming and interfere with air quality. Therefore, the need for the production of biofuels arises, with lignocellulosic residue being a raw material with the potential to assist in this demand. In order to contribute to this In reality, this research used fruit waste to produce bioethanol. Those waste is chemically complex, but biodegradable and contains a large variety of compounds, including fermentable sugars, providing a opportunity for the production of second generation bioethanol. Due to its complex structure, formed by cellulose, hemicellulose and lignin, this biomass requires pre-treatment effective in breaking its structure, in order to allow access to fermentable sugars which will be used later by microorganisms in the fermentation process. Initially, this research used waste from an orange juice industry to test the efficiency of physical, chemical and enzymatic treatments to access the maximum amount of reducing sugars (ARs), reaching results of 69.17 mg/mL in the pre-treatment carried out with sulfuric acid (H2SO4) in autoclave and 61.12 mg/mL from enzymatic hydrolysis. After obtaining the results of ARs in orange biomass, we moved on to the second stage of the research, where the process was carried out using residues from other fruits, such as banana, apple, mango and papaya. The biomass was prepared and subjected to enzymatic hydrolysis by 8 enzymes different, thus obtaining the generation of 268.08 mg/mL of ARs in banana residue, being which with the fermentation process generated bioethanol concentrations of up to 31 g/L. The results obtained confirm the efficiency of the pre-treatments tested, with enzymatic hydrolysis being the more efficient for obtaining reducing sugars, as it allows the release of sugars from complex chains, facilitating fermentation by yeast. Among the biomasses tested, that of banana stood out both for the yield of reducing sugars and for the generation of bioethanol, proving to be a potential residue for this purpose, also taking into account the current availability.